Factors Affecting the Quality of Life of the Elderly in the Working Area of Medan Denai Public Health Center in 2025 - Siegal, Yosphine Sol; Taruli R Sinaga; Jasmen Manurung; Donal Nababan; Henny Arwina Bangun (JURNAL KESMAS DAN GIZI (JKG), 2025)
The aging process results in muscle weakness, physical decline, and various degenerative diseases. These factors significantly affect the quality of life of the elderly, as they reduce independence and force them to rely on others for assistance. This study aimed to analyze the factors affecting the quality of life of the elderly in the working area of the Medan Denai Public Health Center in 2025. A quantitative research approach with a descriptive correlational design was used. The research was conducted from July 2024 to January 2025 at the Medan Denai Health Center. The sample consisted of 143 elderly individuals selected through accidental sampling, specifically those who visited the health center for treatment or consultation. The results showed a significant relationship between quality of life and several variables: gender (p = 0.001), marital status (p = 0.000), income (p = 0.005), stress (p = 0.005), social interaction (p = 0.007), and family support (p = 0.001). The most dominant factor influencing the quality of life was family support. Therefore, it is recommended that the elderly receive sufficient support to remain active and independent in their daily activities. Social interaction with peers should be encouraged to prevent loneliness, which could lead to stress. Furthermore, providing educational support and involving retired or non-working elderly in light, non-competitive, and deadline-free tasks can enhance their sense of productivity and usefulness within the family. Health centers are encouraged to continue supporting the elderly and to conduct family education programs to promote independence and activity among elderly individuals in their daily routines